Architects of Globalism : Building a New World Order during WWII - Hearden, Patrick J., 1942- (Book collections on Project MUSE., 2002)
"Architects of Globalism provides the first comprehensive analysis of American blueprints for the reconstruction of the world after the defeat of Hitler and his allies. Working closely with Roosevelt and Truman, State Department officials assumed primary responsibility for drafting these plans. Hearden shows that while bitter rivalries frequently divided these officials, there was remarkable agreement among them on fundamental principles. These architects of globalism sought to create a liberal capitalist world system, in which foreign markets would absorb the surplus products of American farms and factories so that the United States would be able to maintain high levels of employment without further government intervention in the economy."--Jacket.